Computer model to predict electron beam-physical vapour deposition (EB-PVD) and thermal barrier coating (TBC) deposition on substrates with complex geometry - Pereira, Vitor Emanuel M. Loureiro S. (Cranfield University, 2000)
For many decades gas turbine engineers have investigated methods to improve engine efficiency further. These methods include advances in the composition and processing of materials, intricate cooling techniques, and the use of protective coatings. Thermal barrier coatings (TBCs) are the most promising development in superalloy coatings research in recent years with the potential to reduce metal surface temperature, or increase turbine entry temperature, by 70-200°C. In order for TBCs to be exploited to their full potential, they need to be applied to the most demanding of stationary and rotating components, such as first stage blades and vanes. Comprehensive reviews of coating processes indicate that this can only be achieved on rotating components by depositing a strain-tolerant layer applied by the electron beam-physical vapour deposition (EB-PVD) coating process. A computer program has been developed in Visual c++ based on the Knudsen cosine law and aimed at calculating the coating thickness distribution around any component, but typically turbine blades. This should permit the controlled deposition to tailor the TBC performance and durability. Various evaporation characteristics have been accommodated by developing a generalised point source evaporation model that involves real and virtual sources. Substrates with complex geometry can be modelled by generating an STL file from a CAD package with the geometric information of the component, which may include shadow-masks. Visualisation of the coated thickness distributions around components was achieved using OpenGL library functions within the computer model. This study then proceeded to verify the computer model by first measuring the coating thickness for experimental trial runs and then comparing the calculated coating thickness to that measured using a laboratory coater. Predicted thickness distributions are in good agreement even for the simplified evaporation model, but can be improved further by increasing the complexity of the source model.